2003
DOI: 10.1159/000072735
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Etoricoxib in Primary Dysmenorrhea: Results of a Randomized, Controlled Trial

Abstract: Objective: To determine the efficacy of etoricoxib in the treatment of primary dysmenorrhea. Methods: Seventy-three women were randomly assigned to receive single oral doses of etoricoxib 120 mg, placebo, or naproxen sodium 550 mg at the onset of moderate to severe pain associated with menses. During 3 consecutive menstrual cycles in this double-blind, 3-period, crossover study, pain intensity and pain relief were assessed over the 24-hour period following dosing, and global ratings of therapy were made at 8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
0
18
1
2
Order By: Relevance
“…[12][13][14][15][16] In a dose-ranging study using the postoperative dental pain model, 120 mg was found to be the minimal dose with maximal efficacy of the doses studied, including 60, 180, and 240 mg; etoricoxib 120 mg was superior to 60 mg whereas the 180 and 240 mg doses provided no additional efficacy. 14 The same study has also shown that etoricoxib 120 mg was superior to ibuprofen 400 mg in a single dose comparison according to the primary endpoint, total pain relief over 8 hours, although it should be noted that the maximal daily dose of ibuprofen is 2400 mg taken as 600 mg 4 times a day, which is the regimen included as an active comparator in this study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[12][13][14][15][16] In a dose-ranging study using the postoperative dental pain model, 120 mg was found to be the minimal dose with maximal efficacy of the doses studied, including 60, 180, and 240 mg; etoricoxib 120 mg was superior to 60 mg whereas the 180 and 240 mg doses provided no additional efficacy. 14 The same study has also shown that etoricoxib 120 mg was superior to ibuprofen 400 mg in a single dose comparison according to the primary endpoint, total pain relief over 8 hours, although it should be noted that the maximal daily dose of ibuprofen is 2400 mg taken as 600 mg 4 times a day, which is the regimen included as an active comparator in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Patients scored their pain intensity on a 0 to 3 categorical scale (0, none; 1, slight; 2, moderate; 3, severe) and pain relief on a 0 to 4 categorical scale (0, none; 1, a little; 2, some; 3, a lot; 4, complete) at 16 prespecified time points (15,30,45, 60, 90 min, 2 to 8, 10, 12, 20, and 24 h) in their diaries, during the 24-hour time period after the ingestion of study medication. At 6 hours and 24 hours post dose, the patients provided global assessments of the study drug on a 0 to 4 categorical scale (0, poor; 1, fair; 2, good; 3, very good; 4, excellent).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents have the potential to provide efficacy that is similar to that of recommended doses of opioids, but without the opioid-related side effects that can hinder a patient's recovery from dental or surgical procedures. Etoricoxib is a new COX-2 selective inhibitor that has been shown to be effective in the management of acute pain associated with dental surgery, orthopedic surgery, acute gouty arthritis, and primary dysmenorrhea [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…В ходе клинических исследований показана эф-фективность препарата в лечении острых (первичная дисме-норея, подагрический артрит, боль, связанная со стоматоло-гическими операциями) и хронических (остеоартроз, ревма-тоидный артрит, анкилозирующий спондилоартрит, хрониче-ская боль в спине) болевых синдромов [42,[44][45][46][47][48][49][50]. В частно-сти, при ревматоидном артрите эторикоксиб в дозе 90 мг 1 раз в сутки оказался эффективнее плацебо и напроксена в дозе 500 мг 2 раза в сутки.…”
unclassified